Farm Recording Kelompok Tani Timbul Karya Kecamatan Paliyan Kabupaten Gunungkidul - Agus Dwi Nugroho; Pinjung Nawang Sari; Ken Suratiyah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
Farmers group of “Timbul Karya” has variousassets being rent yet systematically recorded. This community service activity aims to help the farmer group for: (1) preparing the rental activities form filling of assets withitsraining and (2) analyzing the feasibility of soybean farming of the farmer group. Methods used in this community service are training and mentoring. Mentoring is done on making asset management form and analyzingthe farming feasibility, while the training is done with administrative management subject. The administration form consists of on farming activities, save and loan of paddy grain, rental of farm equipment, and rental of partyequipment. The training activity to give a performance description of the group empowerment. The results of the analysis of soybean farming provide R/C value of 2.81 which means that the farming were profitable. Farming analysis also shows that the increasing of soybean production can be solved by enlarge the planted area and the use of urea fertilizer. In addition, given advice to review the increase in revenues, government should giving high soybean prices shifting as well as providing assistance for the production facilities to reduce the productioncost.